HP Cet and Swift J0820.6–2805: two candidate intermediate polars observed by XMM–Newton. Issue 2 (31st August 2020) - Nucita, A A; De Paolis, F; Strafella, F; Licchelli, D
ABSTRACT: We report on the XMM – Newton observation of HP Cet and Swift J0820.6–2805, two X-ray photon sources that are candidates to be members of the intermediate polar class of cataclysmic variables. If the historical optical light curve of HP Cet shows a periodic feature at ≃96 min, a clear identification of such a signature in the high energy band (apart for a variability on a time-scale of ≃8 min as detected by the ROSAT satellite) is lacking. By using XMM – Newton archive data, we clearly identify a feature (at ≃88 min) which is marginally consistent with one of the binary system orbital periods reported in the literature. We also found a signature of a periodic features on the time-scale of ≃5.6 min. In the case of Swift J0820.6–2805, the intermediate polar nature was previously unclear and the orbital and the white dwarf spin periods were unknown. Here, the 0.3–10 keV data undoubtedly reveal an orbital period and a white dwarf spin of ≃87.5 and ≃27.9 min, respectively. The spectral analysis showed that both HP Cet and Swift J0820.6–280 are members of the underluminous IP subclass since their luminosity in the 0.3–10 keV band is estimated to be ≃5 × 10 30 and ≃3.8 × 10 29 erg s −1, respectively.